Bidirectional modulation of infralimbic dopamine D1 and D2 receptor activity regulates flexible reward seeking - Barker, Jacqueline M.; Torregrossa, Mary M.; Taylor, Jane R. (Frontiers in Neuroscience, 2013)
The development of addictive behavior is marked by a loss of behavioral flexibility. In part, this is due to an increase in the ability of environmental stimuli to elicit responding and decreased importance of the action-outcome relationship in behavioral control. It has previously been demonstrated that both inactivation of and dopamine infusions in the infralimbic prefrontal cortex (PFC) can restore behavioral flexibility in paradigms measuring habitual reward seeking. Here, we investigated the mechanism by which cortical dopamine would act to enable goal-directed actions after the transition to habitual behavior has been established. Further, we extended this work to include a novel mouse model of compulsive behavior in which we assessed reward seeking despite the possibility of adverse consequences. Our data show that dopamine receptor D1 inhibition or D2 activation both promote the expression of a flexible responding after the development of habitual or compulsive-like behavior, and we suggest that the ability of DA infusions in the infralimbic PFC to restore sensitivity to changes in outcome value depends on activation of dopamine D2 receptors.